RbCN3H4 and CsCN3H4: A Neutron Powder and Single‐Crystal X‐ray Diffraction Study. Issue 7 (27th May 2013) - Hoepfner, Veronika; Jacobs, Philipp; Sawinski, Peter Klaus; Houben, Andreas; Reim, Johannes; Dronskowski, Richard
Abstract Rubidium guanidinate, RbCN3H4, is the first example of a new class of compounds containing the unsubstituted guanidinate anion CN3H4–. While the first crystal‐structure determination was based on powder X‐ray diffraction, neutron powder and single‐crystal X‐ray diffraction have now been utilized to improve the previous structural model, in particular with respect to experimentally localizing the hydrogen positions, which were so far derived from density‐functional calculations. Furthermore, the molecular structure of the guanidinate anion at room temperature has been refined. All anisotropic displacement parameters, including those of the hydrogen atoms, have been derived from the neutron powder diffraction data, but no rigid‐body movement of the guanidinate anion is present. Additionally, we report the synthesis and structural data of CsCN3H4 crystallizing in the RbCN3H4 type.